(untitled) (Medical Forum Monthly, 2024)
Objective: The study aim was to evaluate whether elective colon and rectal surgery can be safely performed without preoperative mechanical bowel preparation. Study Design: Cross sectional study Place and Duration of Study: This study was conducted at the Sindh Govt. Lyari General Hospital karachi from March 2018 to March 2019. Materials and Methods: A total population of 100 patients admitted for colon and rectal resections were prospectively randomized into two groups .Group A had mechanical bowel preparation before surgery and Group B underwent surgery without preoperative mechanical bowel preparation. Our investigation team followed up for 30 day for wound, anastomotic and intra-abdominal infections and subsequent problems. Results: It was detected that out of 100 patients , after randomization 50 in Group A and 50 cases in Group B were studied in which the anastomotic leak, re-operation rate and mortality were 24%, 10% and 4% in Group A vs 16%, 6% and 6% in Group B respectively. And the hospital stay was 12 and 9 day in Group A vs Group B. However the resulting complication rates were similar in both the groups with Cardiovascular complications , deep Abscess, incisional hernia ,peritonitis and wound infection at 48%, 36%,45%,44%,54% in Group A and 52%, 64% , 55%, 56%, and 46% in Group B. Conclusion: As per our study, we conclude that mechanical bowel preparation doesn’t cause any harm and it’s safe for patients undergoing elective colorectal surgery to undergo without mechanical bowel preparation.